Comparative Effects of Estrogen and Phytoestrogen, Genistein on Testicular Activities of Streptozotocin-Induced Type 2 Diabetic Mice. (September 2019) - Verma, Rachna; Samanta, Rusa; Krishna, Amitabh
The aim of this study was to compare the effect of synthetic estrogen (E2) with a phytoestrogen and genistein in ameliorating type 2 diabetes mellitus (T2D)-mediated testicular dysfunction in mice. The streptozotocin (STZ)-induced type 2 diabetic mice were treated exogenously with either E2 or genistein for 2 durations and compared their effects on testicular activities, serum glucose, and insulin level. Type 2 diabetic mice treated with E2 for only short term (14 days) improved regressive changes in the testicular histology by increasing testosterone synthesis and improving insulin sensitivity, whereas those treated for longer duration (28 days) failed to improve testicular dysfunctions. On the other hand, genistein treated for both short- and long term was useful in improving T2D-induced adverse effects on testicular functions. This study further suggests that treatment with genistein improves spermatogenesis in type 2 diabetic mice by increasing insulin-induced formation of lactate and antioxidative enzymes, which contributes to prevent germ cell apoptosis. Thus, genistein can be used to ameliorate T2D-induced testicular dysfunction.